Um ambiente para simulação de dinâmica e controle de robôs com animação em 3D - Vilarinho, Alessandra Aguiar (2003)
This work shows the use of the rigid body dynamic’s theory and the classic control’s theory as a base for simulation of robots. The simulation’s results are presented in an animation, in three dimensions, of the geometric model of the robot. This work uses theories and tools of Physics, Mathematics, Automation and Computation to solve a robotic’s problem: control and dynamic’s robot computational simulation with three dimensions animation.